2013
DOI: 10.1111/1574-6968.12301
|View full text |Cite
|
Sign up to set email alerts
|

gadAgene locus inLactobacillus brevisNCL912 and its expression during fed-batch fermentation

Abstract: Normally, Lactobacillus brevis has two glutamate decarboxylase (GAD) genes; gadA and gadB. Using PCR, we cloned the gadA gene from L. brevis strain NCL912, a high yield strain for the production of gamma-aminobutyric acid (GABA). However, despite using 61 different primer pairs, including degenerate primers from conserved regions, we were unable to use PCR to clone gadB from the NCL912 strain. Furthermore, we could not clone it by genomic walking over 3000 bp downstream of the aldo-keto reductase gene, a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Interestingly, Enterococcus avium 352 has three GADs, and most Lb. brevis strains contain two distinct GAD encoding genes [1,30,53,54]. It is worth noting that the names of two GAD-encoding genes in Lb.…”
Section: Gad System Of Labmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Enterococcus avium 352 has three GADs, and most Lb. brevis strains contain two distinct GAD encoding genes [1,30,53,54]. It is worth noting that the names of two GAD-encoding genes in Lb.…”
Section: Gad System Of Labmentioning
confidence: 99%
“…One gad gene (gadB) is located in an operon with gadC. However, the other gad gene (gadA) has a far genetic distance with those from other LAB and is located separately from the other gad genes [1,16,30,54]. GadA and GadB have only about 48% identity in amino acid sequences; however, the PLP-binding domain where the active site residues of both GADs are highly conserved.…”
Section: Gad System Of Labmentioning
confidence: 99%
“…Nevertheless, L-598, LD12 and LS24 presented pH values lower than 4.5, presenting significantly lower (p < 0.05) concentrations of GABA compared to the FM with L-571 or L-572 strains. In these particular cases, the low GABA production may be associated with other factors, such as their optimum growing conditions (Minervini et al 2009) or the expression of the GAD enzyme of the strains (Li et al 2013). In addition, some authors have suggested that in some strains, there may be deficiencies in the transport system of glutamate-GABA towards the inside and outside of the cell (Feehily and Karatzas 2013) or that the assimilated glutamate could be used in other metabolic pathways, which would limit the production of GABA (Fernandez and Zuniga 2006).…”
Section: Gaba Quantification In Fmmentioning
confidence: 99%
“…brevis is based on one previous comparative study where single but a different GAD gene (gadA) in the intact operon has been amplified from high GABAproducing Lb. brevis NCL912 (Li et al, 2013). In general, the gadA-encoding GAD from Lb.…”
Section: High Gaba-producing Lactobacillus Brevismentioning
confidence: 99%